Highly sensitive gas sensor using graphene doped with ZnO nanosheet for detection of NO2 gas - Lee soyoung; NAM, YUN SIK; LEE, KANG BONG (대한화학회, 2020)
The current research is focusing on the charateristic of ZnO nanosheets on graphene using spin coating technique for the fabrication of NO2 gas sensors. Physical properties for graphene composite doped with ZnO nanosheet have been intensively investigated using electron microscopy and various spectroscopies. Doping with ZnO nano sheets induced to change electronic properties of graphene, and it led to alter drastically resistivity of graphene in the presence of NO2 gas. Graphene doped with ZnO nano sheets demonstrated the ability to sense NO2 gas sensitively with the saturation time is around 400s, and with the limit of detection being below 0.15ppm. In comparison with other gases, to which the highest response was 33%, this sensor has very good selectivity and repeatedly.